Knowledge And Awareness Regarding Needle Stick Injuries Among Health Care Workers in Tertiary Care Hospital in Ahmedabad, Gujarat - Rakesh Shah; H.K. Mehta; Manish Fancy; Sunil Nayak; Bhavesh N. Donga (Medsci Publications, 2010)
Health care professionals are exposed to variety of dangers like infections, cuts and needle stick injuries, exposure to anesthetic gases, radiations, dermatitis causing substances, vaccines, serums etc. This study focuses on issues related to some of these risks and possible ways and means on how to overcome these risks. Objective: To assess the knowledge, attitude and practices among health care workers about needle stick injury. Materials and Methods: A cross-sectional study was carried out in a teaching hospital in June 2008. Results: Mean age of Health care workers was 33.5 years, majority (50%) in the age group of 20-30 years.  61% HCWs had less than 5 year of work experience. 67% HCWs had received hepatitis B vaccination of which only 17.9% had carried out Anti HBs antibody check up. Knowledge about disease transmitted by NSIs was satisfactory. Though 36% had suffered Needle stick injury (NSIs), only 8.3% reported the incident of NSIs. 81% HCWs know about universal precaution guidelines. Conclusion: There is an urgent need for strengthening skills, developing newer competencies and broadening our knowledge in occupational health and safety and disaster management.